Pengaruh Modal Usaha, Kompetensi Kewirausahaan dan Pendapatan Terhadap Keberlangsungan Usaha Pelaku UMKM di Kecamatan Toapaya Kabupaten Bintan - Paramita, Bunga; Citra Indah Kirana, Reneta (Program Studi Manajemen FEBM UMRAH, 2024)
The purpose of this study was to determine the effect of Business Capital, Entrepreneurial Competence and Income on Business Sustainability of SMEs Actors in Toapaya District, Bintan Regency. The research object in this study is SMEs actors in Toapaya District. The method used in this research is Quantitative Method with data collection techniques using a questionnaire, the sampling technique in this study used Simple Random Sampling. With a population of 213 SMEs players in Toapaya District, the sample in this study was 120 samples. The data analysis technique uses multiple linear regression analysis so that the results of the study are found, namely Personally, the Business Capital Variable has a positive and significant effect on the Business Continuity of SMEs Actors with a Thitung value (4.608> 1.980), the Entrepreneurial Competency Variable has a positive and significant effect on the business continuity of SMEs Actors with a Thitung value (2.177> 1.980) and the Income Variable has a positive and significant effect on the Business Continuity of SMEs Actors with a Thitung value (3.990> 1.980). While simultaneously the variables of business capital, entrepreneurial competence and income have a positive and significant effect on the business continuity of SMEs actors in Toapaya District, Bintan Regency.